Constitutions of the Chapter of Samogitian Cathedral: Letter, Spirit, Life - Jovaiša, Liudas (Vilnius University Open Series, 2024)
The aim of the paper is to examine implementation of the laws of the cathedral chapter of the diocese of Samogitia according to the acts of the general sessions of the chapter (for the period from 1613 to 1913). The corpus of the constitutions, or statutes of the chapter was created in 1561–62 by the famous mid-16th century Lithuanian lawyers, Canon Pedro Ruiz de Moros (Petrus Roysius) and Bishop Joannes Domanowski. Despite the fact that already in 1637 Bishop Georgius Tyszkiewicz added some new constitutions (published in the annex of the paper), and there were subsequent attempts to ‘modernize’ the old corpus of the constitutions in the late 18th – early 19th century, the Roysian statutes retained their validity and exceptional authority in the life of the Samogitian cathedral chapter as long as 1925 when the old statutes were fundamentally revised. The constitutions predominantly influenced decisions of the chapter via hearing and memory. Due to the limited copies of the text which had to be not too much multiplicated in order to preserve secrecy, majority of canons were aware of the contents of the constitutions from reading aloud (usually, in fragments than in extenso) during the general sessions of the chapter. Perhaps this could explain occasional cases of erroneous allusion to the text of the constitutions in the decisions of the chapter. In some other cases, aspiration to ground the decisions of the chapter with solid arguments could inspire canons to invoke hardly definable ‘spirit’ (mens) of the constitutions. However, usually the constitutions were quoted correctly; the cases of clear reference to specific articles of the constitutions found in the acts of the general sesssions of the chapter are listed and described in the final part of the paper.